The Communication Strategy of The Directorate of Drugs Police Sumatera Utara in an Effort to Eradicate Drugs - Mursyida, Shania; Saragih, M. Yoserizal (LPPM IAIN Parepare, 2022)
Drug abuse is still a considerable problem today considering the consequences of the development of science and technology, the impact of globalization, the flow of transport is very rapidly growing and the transfer of materialistic values with the dynamics of the purpose of bad opinion that led to the spread of drugs to urban areas but also to rural areas. This study aims to determine the communication strategy used by the Direktorat Reserse Narkoba Polda Sumut in this case eradicating drugs. This study uses the theory of organizational communication with descriptive qualitative research methods. Data collection techniques used are observation, in-depth interviews and documentation. The results of this study concluded that the Direktorat Reserse Narkoba Polda Sumut has a strategy or way of working to achieve the goals in the Direktorat Reserse Narkoba Polda Sumut, with various ways such as the dissemination of News, providing the media as a place to provide information.